The effect of heat stress on the hindgut microbiota and metabolites of Simmental heifers - Gao, Liutao; Zhang, Zhipeng; Li, Pengtao; Liu, Ziying; Li, Minjie; Li, Ruoxi; Tian, Quanzhao; Zheng, Zhuo (Frontiers in Microbiology, 2026)
IntroductionHeat stress adversely affects the physiological status and productive performance of cattle; however, the mechanisms underlying heat stress-induced alterations in the hindgut microbiota and its metabolic functions remain poorly understood, particularly in beef-type Simmental cattle.MethodsIn this study, Simmental heifers were exposed to heat stress, and physiological parameters and blood biochemical indices were evaluated. Hindgut microbial composition was characterized using 16S rRNA gene sequencing, and metabolic profiles were analyzed using liquid chromatography-mass spectrometry (LC-MS)-based metabolomics.ResultsHeat stress significantly increased respiratory rate and rectal temperature and induced marked changes in several blood parameters, including heat shock proteins. 16S rRNA sequencing revealed significant alterations in the relative abundance of multiple bacterial genera under heat stress, including Ruminococcaceae_UCG-013, Alistipes, Clostridium_sensu_stricto_1, Flavonifractor, Dorea, and Anaerovorax. Metabolomic pathway enrichment analysis identified seven significantly affected pathways: pyrimidine metabolism, biosynthesis of unsaturated fatty acids, amino sugar and nucleotide sugar metabolism, fatty acid biosynthesis, propanoate metabolism, inositol phosphate metabolism, and beta-alanine metabolism.DiscussionThis study provides one of the first comprehensive characterizations of heat stress-associated alterations in the hindgut microbiota and metabolome of Simmental beef cattle. The findings suggest that heat stress disrupts the hindgut microbial ecosystem by reducing beneficial taxa and increasing potentially harmful bacteria, which may be linked to disturbances in host energy metabolism and physiological homeostasis.